2015
DOI: 10.1074/jbc.m114.603142
|View full text |Cite
|
Sign up to set email alerts
|

Specific Activation of Insulin-like Growth Factor-1 Receptor by Ginsenoside Rg5 Promotes Angiogenesis and Vasorelaxation

Abstract: Background:The mechanism by which ginsenoside Rg5 regulates vascular function remains unclear. Results: Rg5 increases angiogenesis and vasorelxation by activating multiple signal transduction pathways downstream of insulin-like growth fastor-1 receptor (IGF-1R). Conclusion: Rg5 promotes endothelial cell function through activation of IGF-1R. Significance: These findings reveal a mechanism for the positive regulation of vascular function by Rg5-mediated IGF-1R activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Besides, the VEGF pathway is recognized as the key regulators of the angiogenic process23. Previous studies have also presented vascular smooth muscle contraction signaling pathway24, JAK/STAT1 signaling pathway25, insulin signaling pathway26 and ErbB signaling pathway27 played important roles in angiogenesis. To adapt to the development of loach posterior intestine, such as cell size growing, cell proliferation and migration, the pathways associated with cytoskeleton were found.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the VEGF pathway is recognized as the key regulators of the angiogenic process23. Previous studies have also presented vascular smooth muscle contraction signaling pathway24, JAK/STAT1 signaling pathway25, insulin signaling pathway26 and ErbB signaling pathway27 played important roles in angiogenesis. To adapt to the development of loach posterior intestine, such as cell size growing, cell proliferation and migration, the pathways associated with cytoskeleton were found.…”
Section: Discussionmentioning
confidence: 99%
“…The ginsenosides, which consist of triterpene aglycones, are classified into three major categories: panaxidiols, panaxatriols, and oleanolic acid derivatives [2]. Recently, ginsenosides and their derivatives have been reported to show antioxidant [3,4], anti-inflammatory [5][6][7], anti-obesity [6,8], angiogenic [3,9,10], and anticancer activities [11][12][13][14]. The ginsenoside Rh2 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation sites have been identified in the intracellular domain of IGF-1R, which allow for specific binding and modulation of multiple downstream effectors [27,28]. An earlier study by Wang et al confirmed that low shear stress-induced IGF-1R phosphorylation modulates smooth muscle cell behavior and functions (proliferation and phenotype) via enhancing Akt activation [29].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 66%